How content area teachers mark written work implications for language curriculum and instruction - Martin, Isabel Pefianco (Philippine Journal of Linguistics, 2003)
In designing English language courses, we often take into account the needs of students, as well as of other stakeholders in the academic community. One such stakeholder is the content area teacher, who is traditionally viewed as a beneficiary of effective English language teaching (ELT). Using a survey, this paper looks into how these content area teachers mark their students' written work. The survey hopes to determine the criteria used by these teachers in grading reports and essays. As the writer analyzes how content area teachers mark written work, she also hopes to draw implications for English language curriculum and instruction in Ateneo de Manila University. In the end, it is argued that content area teachers are not just beneficiaries of ELT; they are also active partners of English language teachers.